Technology of foam concrete on composite knitting with hydroremoval ashes - Irina Nikolaevna Kuznetsova; Marina Alekseevna Raschupkina (Вестник СибАДИ)
In this article an attempt to provide an advanced method of production of foam concrete is made. The advanced production technology of foam concrete on composite knitting with content of the high-disperse particles of ashes of hydroremoval received by crushing of particles of ashes allows to make constructional and heat-insulating material, using production wastes TEC. The received results of heatphysical and mechanical properties of ashes as high-disperse additive and foam concrete samples are provided and proved.